Mercadorização da educação: elementos que circunscrevem a formação inicial de professores - Vale, Rosiney Aparecida Lopes do [UNESP] (2015)
Studies about initial teachers education, as well as curriculum and pedagogical theories, have become recurrent in academic work, research groups, discussion forums, conferences etc. and have raised different positions. For this reason, the main goal of this work is to investigate the pedagogical trends in teachers education that underlie the Pedagogical Plan of the Course of Letras (PPC 2014), from the Center of Letras, Communication and Arts in the State University of North Paraná, campus in Jacarezinho∕PR (CLCA∕CJ), and to indicate the characteristics of this model of development. The questions that guided the present research were: Which pedagogical theories underlie the development of the PPC 2014 of the CLCA? And what is the profile (type) of teacher, resulting from this education? The specific goals were: a) to identify the pedagogical trends that underlie the PPC 2014 of the course of Letras at the CLCA; b) to summarize the profile of the future teacher, resulting from this education; c) to investigate high school graduates' concept of school education, considering those whose teachers graduated with a Bachelor's degree in Letras, which curriculum design was oriented by the current National Curricular Guidelines (DCNs); d) to discuss if the pedagogical theories underlying the PPC 2014 provide conditions for the egress to critically engage in teaching, adopting the ideals of an education committed to teaching and promoting human emancipation. Therefore, we sought to present and discuss the concepts of different curriculum and pedagogical theories, and issues related to the mercantilization of scholl education, in the current context, as elements that circumscribe the initial teachers education. This work presents, then, results of a bibliographical research and documentary analysis, based on the qualitative approach, which data were analysed according to content analysis technics. The results of the research generated...